GABA(A) receptor mediated transmission in the thalamic reticular nucleus of rats with genetic absence epilepsy shows regional differences: Functional implications - ONAT, FİLİZ; YANANLI, HASAN RACİ; GÜLHAN, REZZAN; ŞEHİRLİ, ÜMİT SÜLEYMAN (ELSEVIER SCIENCE BV, 2006)
The aim of the present study was to investigate the effect of local injections of the GABA(A) receptor antagonist, bicuculline, into the rostral and caudal parts of the thalamic reticular nucleus (TRN), on the generation of spike-and-wave discharges in Genetic Absence Epilepsy Rats from Strasbourg (GAERS). Spike-and-wave discharges are important in the pathophysiology of absence epilepsy and generated by the cortico-thalamo-cortical pathway, where GABA has a significant role, particularly in the TRN. Artificial cerebrospinal fluid or bicuculline was administered to rostral or caudal parts of TRN of GAERS through a stereotaxically placed guide cannula. Administration of bicuculline produced opposite effects according to the injection site. Administration into the caudal TRN produced statistically significant increases in the duration of spike-and-wave discharges, whereas injections into the rostral TRN produced significant decreases. Correspondingly, distinct patterns of afferent connections have been demonstrated with the wheat-germ-agglutinin horseradish peroxidase (WGA-HRP) retrograde tracing method in control non-epileptic rats and GAERS for the rostral and caudal parts of the TRN. Injection of WGA-HRP tracer showed no detectable difference regarding the rostral and caudal connections between GAERS and Wistar animals. Rostral parts of TRN have thalamic and cortical connections that are primarily motor and limbic whereas for the caudal parts these connections are primarily sensory. Further, the rostral parts receive inputs from the substantia nigra pars reticularis and the ventral pallidum that the caudal part lacks. The extent to which these connectional differences may be responsible for the functional differences demonstrated by the bicucculine injections remains to be explored. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: bicuculline; GAERS; thalamo-cortical connection; rostral TRN; caudal TRN; LIMBIC MOTOR SEIZURES; HORSERADISH-PEROXIDASE; WAVE DISCHARGES; WAG/RIJ RATS; IN-VITRO; NEURONS; ORGANIZATION; NETWORKS; MODEL; SPIKE